DZIAŁALNOŚĆ SŁUśBY BEZPIECZEŃSTWA WOBEC DUCHOWIEŃSTWA NA ZIEMI LUBUSKIEJ W LATACH SIEDEMDZIESIĄTYCH XX WIEKU CASUS KSIĘDZA KAZIMIERZA PIECHOWIAKA - Cezary Pieńkowski (In Gremium. Studies in History, Culture and Politics, 2012)
THE ACTIVITY OF THE SECURITY SERVICE TOWARDS THE CLERGY IN LUBUSKIE PROVINCE IN THE 1970’s. THE CASE OF KAZIMIERZ PIECHOWIAKThe history of the Catholic Church in Poland in the times of communism interests professional historians as well as journalists as it is one of the most significant parts of the political history of the People's Republic of Poland (PRL). The confrontation of the strongly organized and popular church with the based on Marxist-Leninist ideology state had to create a conflict the course of which, different than in other communistic countries, became one of the most important factors determining the Polish model of real socialism. This article provides an analysis of this conflict in Gorzów diocese in the 1970s. The security service tried do influence the clergy in numerous ways. A wide range of actions, from promises of speeding up decisions of authorities to threats of disclosing discrediting materials, was employed. However, the efficiency of secret collaborators varied as some priests passed on information they found in pastoral letters or the press. They even sometimes refused to carry out some tasks. Not so long ago, in 1966 the chief of the security service in Zielona Góra stated that they did not guarantee the fulfilment of operational tasks within the Church.Kazimierz Piechowiak, a.k.a. “Franek”, the parish priest in Kolsko was a long-time collaborator of the security service. He was recruited by Władysław Długosz, the chief of PUBP in Człuchów, with the use of discrediting materials. The priest was eager to cooperate for what he additionally received remuneration. The security service valued his operational activity. His was said to carry out his tasks properly and present a positive attitude towards the officers of the security services. The materials he delivered provided general information on priests' meetings, the situation of the clergy and instructions received from the Curia. The services' collaboration with “Franek” did not cease even after his retirement as they believed it would be a shock for him. Therefore, officers kept meeting with him until his death.